Peran Pemerintah dalam Menjaga Stabilitas Ekonomi Makro di Tengah Krisis Energi - Ahmad Wahyudi Zein; Ayla Rizki Janira; Indah Amelia; M. Farhan Aulia Rozan; Nia Rahmadhani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study focuses on the global energy crisis, which has exerted significant pressure on the Indonesian economy in recent years. Rising energy prices have directly contributed to higher inflation, increased production costs, and growing fiscal burdens for the government. Under these conditions, the government plays a crucial role in maintaining macroeconomic stability to prevent energy-related shocks from escalating into a broader economic crisis. This study aims to analyze the role of government policies in sustaining macroeconomic stability amid the energy crisis. A qualitative approach is employed through a literature review of relevant scholarly sources. The findings indicate that fiscal, monetary, and energy policies complement each other in mitigating the impacts of the crisis. However, their effectiveness largely depends on policy consistency and the government’s capacity to maintain long-term fiscal balance.